Infant oral health care: An invaluable clinical intervention - Kanika Singh Dhull; M D Indira; Rachita Singh Dhull; Bhavya Sawhney (Wolters Kluwer Medknow Publications, 2016)
Dental assessments and evaluations for children during their 1st year of life have been recommended by the American Academy of Pediatric Dentistry and the American Association of Pediatrics. Early dental intervention evaluates a child's risk status based on parental interviews and oral examinations. These early screenings present an opportunity to educate parents about the medical, dental, and cost benefits of preventive rather than restorative care and may be more effective in reducing early childhood caries than traditional infectious disease models. A comprehensive infant oral care program includes: (1) risk assessments at regularly scheduled dental visits, (2) preventive treatments such as fluoride varnishes or sealants, (3) parental education on the correct methods to clean the baby's mouth, and (4) establishment of dental home and use of anticipatory guidance. The present article highlights the important guidelines of infant oral health care.